2014 47th Annual IEEE/ACM International Symposium on Microarchitecture 2014
DOI: 10.1109/micro.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Dodec: Random-Link, Low-Radix On-Chip Networks

Abstract: Abstract-Network topology plays a vital role in chip design; it largely determines network cost (power and area) and significantly impacts communication performance in manycore architectures. Conventional topologies such as a 2D mesh have drawbacks including high diameter as the network scales and poor load balancing for the center nodes. We propose a methodology to design random topologies for on-chip networks. Random topologies provide better scalability in terms of network diameter and provide inherent load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent approaches have shown that irregular topologies adopted in inter-switch networks can significantly reduce the end-to-end latency [4]- [7]. These networks can improve the performance of parallel applications not only for off-chip networks but for on-chip inter-core networks with low-radix routers [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches have shown that irregular topologies adopted in inter-switch networks can significantly reduce the end-to-end latency [4]- [7]. These networks can improve the performance of parallel applications not only for off-chip networks but for on-chip inter-core networks with low-radix routers [8], [9].…”
Section: Introductionmentioning
confidence: 99%